KORELASI ANTARA DISIPLIN BELAJAR DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK KELAS V - Muhammad Iqbal Fenza; Hery Kresnadi; Asmayani Salimi (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the relationship between learning discipline and learningmotivation with student learning outcomes in the thematic learning of class VElementary School 35 South Pontianak. The research method used is descriptivemethod with the form of correlation study research. The subjects in this study were allfifth grade students, totaling 109 students and the sample used was random by taking30% of the population, namely 33 students. The data collection technique used is anindirect communication technique or by means of an intermediary tool by providing aquestionnaire of learning discipline and learning motivation to students and adocumentary technique that uses the average value of thematic learning of fifth gradestudents at SDN 35 South Pontianak. The results showed that the average studentlearning discipline was 77.91, the average student learning motivation was 81.71, theaverage student learning outcome was 75.80, and the correlation between learningdiscipline and learning motivation with results student learning of 0.280. Based onthese data, it can be concluded that there is a low correlation between learningdiscipline and learning motivation with student learning outcomes in the thematiclearning of class V at SDN 35 South Pontianak.Keywords:Correlation, Learning Discipline, Learning Motivation, LearningOutcomes, and Thematic Learning